(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
This article talks about the place of the Mongols in Asia, how they conquered the countries, and the army of Genghis Khan. Genghis Khan created a large, well-armed, well-disciplined and organized army from the Mongols. According to the author of the 13th century, Juvaini, all the Mongolian inhabitants who were engaged in cattle breeding in peacetime were quickly transformed into a regular army consisting of ten, one hundred, one thousand, ten thousand warriors - district units. Each warrior had to prepare in advance the necessary weapons, equipment and horses during the military campaign. The army was led by the head of the army, the head of the thousand, and the head of the district. District units were usually commanded by princes. In addition to the main army, at the discretion of Genghis Khan, a special guard ("guard") made up of military nobles was also established. For this reason, the Mongol troops were defeated in many battles.